PENGEMBANGAN MEDIA PEMBELAJARAN FLIPBOOK INTERAKTIF MATA PELAJARAN PENDIDIKAN PANCASILA KELAS III SD NEGERI 3 KAMPUNG BARU - Eka Widiyantara; I Made Suweta; Putu Yulia Angga Dewi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop interactive flipbook learning media for Pancasila Education subjects in the third grade of SD Negeri 3 Kampung Baru to enhance students' contextual and meaningful understanding. The method used is Research and Development (R&D) with the ADDIE development model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The final product developed is an interactive flipbook media integrated with a quiz based on the Quizizz platform. The research trial subjects involved three classroom teachers and twenty third-grade students. Product validity testing was conducted by three expert validators, comprising a media expert, a material expert, and a language expert. The validation results show feasibility percentages of 97% from the media expert, 98% from the material expert, and 92% from the language expert, with a "very valid" qualification. Furthermore, the practicality test results obtained a score of 100% from teacher responses and 97% from student responses, categorized as "very practical." Based on these results, the interactive flipbook learning media is declared very valid, practical, and feasible for use in the learning process for the "Let's Get to Know Pancasila" material.